Eksistensi Masyarakat Hukum Adat Dalam Pengelolaan Hutan Prespektif Undang-Udang N0mor 41 Tahun 1999 - Muhammad Saleh (Fakultas Hukum Universitas Mataram, 2011)
The forest resources must be save for prosperity the people like in section 33 UUD. The basic rules of benefit forest in Indonesia have be meaning in section 33 article 4 to all the citizenry. UU No 5 1967 about Ketentuan-Ketentuan Pokok Kehutanan have meaning the purpose close by timber management but not just aspiration all of a pattern in the forest management or ecosystem management which accomodation all aspect social culture although economic and continue environmental conservation. Almost all of the places in Indonesia have traditional law like open the forest for agricultural business and the others. Who herds livestock, persecution wild animal and take agricultural produce. And all the area of the forest manage eternal with society traditional law be income their life with all of the ability